Zero-hunger through the lens of food security in populous Asia: pre and post-pandemic - Ashraf, Jawaria; Jun, Ma; Ali, Sumran; Ghufran, Muhammad; Xiaobao, Peng (Frontiers in Sustainable Food Systems, 2024)
Food security is a matter of human existence and a top agenda item of United Nations’ sustainable development goals (SDGs); in the wake of the fact that 2.37 billion people are classified as either undernourished or unable to sustain regular intake of nutrient-dense diet, is a matter of prime importance across the globe. Our study investigated the zero-hunger reality through the prism of food security impacted by the consumption of fixed capital (Agriculture, Forestry and Fishing), environmental temperature surges, arable land, agricultural land, nitrogen and phosphate nutrient usage in the context of the most populous Asian countries. We employed the quantitative approach to investigate our problem by relying on the data collected from the FAOstat, World Bank, Economist Impact, and national statistics bureaus spanning 2016 to 2020 for six Asian countries such as China, India, Indonesia, Pakistan, Bangladesh, and Malaysia. This study’s findings explain that environmental temperature surges and arable land negatively affect food security, while fertilizers and fixed capital consumptions positively impact food security. Moreover, the study findings pave the path for policymakers and businesses to find the best approaches to enhancing food security, hygiene, quality, availability and wealth prosperity in these specific countries, which are half the world’s population, i.e., approximately 4 billion.